(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Patriotism, as the quality characteristic of human subjectness, is the most important condition and source for strengthening the unity, integrated and sustainable development of society and state. And the patriotic position and activity of the citizens of the country largely depend on the level of interest and awareness of the need to include patriotic values in the system of motivations of citizens and create adequate conditions for this. The problem of methodological basis of patriotism still remains one of the most urgent today. This article attempts to analyze the theoretical and methodological problems in the study of patriotism phenomenon. Authors, highlighting such concepts as naturocentrism, sociocentrism and anthropocentrism, show their insufficiency to reveal this phenomenon. The task of this study is, firstly, to show the presence of a certain impropriety in the existing approaches to the basis of patriotism, secondly, to consider patriotism not just as a political and ideological construction and attitude or sensory and emotional complex (as such, it gets, as a rule negative evaluation), but as a way of existence of human activity through inclusion patriotism in philosophical categories and definitions to reveal ontological sources of such existence and specifics of their implementation in specific social-cultural conditions, and thirdly, to identify the main tendencies and problematic cross points in the forming citizens patriotic attitudes and motivations.